A Clinical Study on Etiological Diagnosis of Acute Seizure in Hospitalized Patient - Chowdhury, Ashif Mashud; Kalimullah; Islam, Md Kamrul; Gani, Md Osman; Haque, A K M Aminul; Rahman, Md Ridwanur (Journal of Dhaka National Medical College & Hospital, 2015)
Seizures refer to clinical phenomenon rather then a single disease entity, as there are many forms and causes of seizure to epilepsy. There are a group of disorders whose only one main symptom is seizure whilst other disorders seizure is just one of the manifestations. It is a common presentation of a wide variety of diseases like idiopathic epilepsy, cerebrovascular diseases , ICSOL, metabolic disease (e.g. diabetes mellitus,uremia,hepatic failure etc).Central nervous system infections,electrolytes imbalance or poisoning. Among the diseases Intracerebralhaemorrhage is the most common cause of seizure in this study remaining in the top of the list. Since infectiouscauses are important in seizure etiology, of which most are treatable with a relatively favorable out come, critical evaluation for infectious and early intervention is recommended. J. Dhaka National Med. Coll. Hos. 2015; 21 (01): 48-51